Hans Christian Andersen’s Use of Anthropomorphism - Paludan, Julia Shore (Aktualitet - Litteratur, kultur og medier, 2019)
The topic of anthropomorphism in Hans Christian Andersen’s tales has been discussed with students in classes in Danish Language and Literature at Sapienza, University of Rome (La Sapienza, Università di Roma) both for the purpose of the translation of his works and for understanding the meanings of the imagery in the studied works. Anthropomorphism is a common theme in many of Hans Christian Andersen’s fairy tales. Andersen’s symbolic use of nature, household objects, trinkets, toys and even birds, is an important theme in many of his works. He bestows human emotions on animate and inanimate objects, such as love and envy, often with an added touch of humour or irony. Andersen conveys issues of often sombre or tragicomic content, sometimes through allegorical tales and myths, that although they are not necessarily easily translatable or culturally transferable, appeal universally to all generations and nationalities. Andersen’s personification of animals also provides a subtle disguise for graver issues such as loss, and the struggle for freedom. The use of anthropomorphism and symbolism also allows younger readers access to complex and universal issues.